- #1
Rick16
- 121
- 29
- TL;DR Summary
- relabeling indices
This is exercise 1.8.3 from Foster & Nightingale:
Show that if ##\sigma_{ab} = \sigma_{ba}## and ##\tau^{ab} =-\tau^{ba}## for all ##a##, ##b##, then ##\sigma_{ab}\tau^{ab}=0##.
I began writing down ##\sigma_{ab}\tau^{ab}=\sigma_{ba}(-\tau^{ba})=-\sigma_{ba}\tau^{ba}##. Here I got stuck and looked at the solution in the back of the book. In the solution, the authors use the fact that the suffixes are dummy indices and can be relabeled: ##-\sigma_{ba}\tau^{ba}=-\sigma_{ab}\tau^{ab}##. So they end up with ##\sigma_{ab}\tau^{ab}=-\sigma_{ab}\tau^{ab}##, which can only be true if ##\sigma_{ab}\tau^{ab}=0##.
It seems to me that this relabeling clashes with the definition of the tensors in the problem statement. If I can simply relabel the indices, then what keeps me from relabeling them right away? The skew-symmetric tensor is defined as ##\tau^{ab}=-\tau^{ba}##. Since the indices are dummy indices, I relabel them and write ##-\tau^{ba}=-\tau^{ab}## and I end up with ##\tau^{ab}=-\tau^{ba}=-\tau^{ab}\Rightarrow \tau^{ab}=0.## This would imply that all skew-symmetric tensors are zero, which is certainly not true.
So why can I apply the relabeling in the case of ##\sigma_{ba}\tau^{ba}##, but not in the case of ##\tau^{ba}##? I don’t really see the difference.
Show that if ##\sigma_{ab} = \sigma_{ba}## and ##\tau^{ab} =-\tau^{ba}## for all ##a##, ##b##, then ##\sigma_{ab}\tau^{ab}=0##.
I began writing down ##\sigma_{ab}\tau^{ab}=\sigma_{ba}(-\tau^{ba})=-\sigma_{ba}\tau^{ba}##. Here I got stuck and looked at the solution in the back of the book. In the solution, the authors use the fact that the suffixes are dummy indices and can be relabeled: ##-\sigma_{ba}\tau^{ba}=-\sigma_{ab}\tau^{ab}##. So they end up with ##\sigma_{ab}\tau^{ab}=-\sigma_{ab}\tau^{ab}##, which can only be true if ##\sigma_{ab}\tau^{ab}=0##.
It seems to me that this relabeling clashes with the definition of the tensors in the problem statement. If I can simply relabel the indices, then what keeps me from relabeling them right away? The skew-symmetric tensor is defined as ##\tau^{ab}=-\tau^{ba}##. Since the indices are dummy indices, I relabel them and write ##-\tau^{ba}=-\tau^{ab}## and I end up with ##\tau^{ab}=-\tau^{ba}=-\tau^{ab}\Rightarrow \tau^{ab}=0.## This would imply that all skew-symmetric tensors are zero, which is certainly not true.
So why can I apply the relabeling in the case of ##\sigma_{ba}\tau^{ba}##, but not in the case of ##\tau^{ba}##? I don’t really see the difference.